The relation between serum cytokeratin 18 and acute pancreatitis: Can it be a serological predictive marker? - İrfan KORUK,; Hakan ÖZDEMİR,; Musa Aydınlı,; Mehmet TARAKÇIOĞLU,; Mehmet KORUK, (Turkish Journal of Gastroenterology, 2019)
-